2016
DOI: 10.1021/acs.jpca.6b01261
|View full text |Cite
|
Sign up to set email alerts
|

OH-Radical Oxidation of Surface-Active cis-Pinonic Acid at the Air–Water Interface

Abstract: Gaseous biogenic volatile organic compounds (BVOCs) are immediately oxidized by gaseous oxidants to form BVOC-acids that rapidly condense onto aqueous aerosol phase and thus contribute to the growth of atmospheric particles. Because BVOC-acids are highly hydrophobic and hence surface-active in nature, it seems critical to study the oxidation by gaseous hydroxyl radical (·OH(g)) at the air-water interface. Here we report on the fast (≤10 μs) oxidation of aqueous cis-pinonic acid (C10H16O3, CPA, cis-pinonate ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 92 publications
14
74
0
Order By: Relevance
“…We note that the H-containing nascent phenol and hydroperoxide groups are able to exchange with D 2 O prior to detection B1 ms later. [10][11][12] The finding that m/z = 152 does not shift in D 2 O solvent is clearly consistent with BzO-O 2 peroxyl radical structural isomers.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…We note that the H-containing nascent phenol and hydroperoxide groups are able to exchange with D 2 O prior to detection B1 ms later. [10][11][12] The finding that m/z = 152 does not shift in D 2 O solvent is clearly consistent with BzO-O 2 peroxyl radical structural isomers.…”
Section: Resultssupporting
confidence: 63%
“…Also note that BzO signals do not decay as single exponentials but bottom out at large pulse energies (i.e., at large OH doses). [10][11][12]40 The rate coefficients of ( OH + BzO) via (R 1AB + R 1AD ) and ( OH + OH) via R 9 (Scheme 1) in bulk water are within a factor of two and correspond to diffusionally controlled reactions: k 1AB + k 1AD = 2.5 Â 10 9 M À1 s À1 , k 9 = 5.5 Â 10 9 M À1 s À1 . 3,41,42 Since they are also expected to be fast and commensurate at the air-water interface, the above observations imply that: (1) OH recombination into relatively inert H 2 O 2 (via R9, Scheme 1) is competitive and more extensive than its reaction with BzO in the more dilute 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…times smaller than those at m/z 431 (and 433) from OA at [1-octanol] = [OA] = 100 mM reveals that 1-octanol is much less reactive than OA toward CIs, although both species are expected to have similar affinities for aqueous surfaces. 25,32,43,[69][70] The C 23 ethers and esters produced in each case, by having similar mass and structures (see This finding is in line with gas-phase reaction rate constants of CIs + HCOOH/CH 3 COOH, which approach collisionally controlled values: k ≥ 10 -10 cm 3 molecule -1 s -1 , 22 vs. the much smaller values for CIs + methanol/2-propanol. 48,50,68 Tobias and Ziemann have reported that rate constants of gas-phase C 13 CIs reactions with various species increase in the order: water < methanol < 2-propanol < formaldehyde < formic acid < heptanoic acid, over a 10 4…”
Section: Page 3 Of 23 Acs Paragon Plus Environmentsupporting
confidence: 65%
“…Pfrang et al, 2014;Sebastiani et al, 2015), pinonic acid (see e.g. Enami and Sakamoto, 2016), 1,2-dipalmitoyl-sn-glycero-3phosphocholine (DPPC) (see e.g. Thompson et al, 2010), or nonanoic acid (see e.g.…”
Section: Introductionmentioning
confidence: 99%